One pot synthesis of low cost emitters with large Stokes' shift. (February 2017) - Volpi, G.; Magnano, G.; Benesperi, I.; Saccone, D.; Priola, E.; Gianotti, V.; Milanesio, M.; Conterosito, E.; Barolo, C.; Viscardi, G.
Abstract: A series of 1, 3-diarylated imidazo[1, 5- a ]pyridine derivatives were synthesized in high yields by a one-pot, three components, condensation of phenyl(pyridin-2-yl)methanone with several aldehydes in the presence of ammonium acetate. These compounds were characterized by spectroscopic and crystallographic techniques and their optical properties were discussed in relation to their chemical structures. Absorption and fluorescence spectra generally show two absorption maxima around 310 nm and 350 nm and an emission maximum between 460 and 550 nm with a remarkable Stokes' shift range of 90–166 nm. Moreover, depending on the chemical structure of the substituent in position 3, we were able to tune the quantum yields (Φ) in solution from 6.4% to 38.5%. Finally, the 1-phenylimidazo[1, 5- a ]pyridine substituted with a 3-(2-methoxyphenyl) group (large Stokes' shift, high Φ) was dispersed in a transparent thermosetting polyurethane resin giving a luminescent low cost material. Graphical abstract: Highlights: 1, 3-Diarylated imidazo[1, 5- a ]pyridine derivatives. Successful one-pot synthesis in high yields. Large Stokes' shifts (more than 100 nm) and fluorescence quantum yields up to 38.5%. Optical properties of a promising compound was investigated in polyurethane resin. Molecular structure and packing in the crystal structure for three compounds.